2013
DOI: 10.12674/ptk.2013.20.4.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Craniocervical Flexion on Muscle Activities of Abdominal and Cervical Muscles During Abdominal Curl-Up Exercise

Abstract: 1)Abdominal curl-up exercise may excessively increased superficial neck flexor such as sternocleidomastoid (SCM) muscle. Also, the muscle activity of the abdominal muscles haven't investigated during abdominal curl-up with craniocervical flexion (CCF). Therefore, the purpose of our study was to determine the effect of CCF on the muscle activity of the abdominal and SCM muscles during abdominal curl-up. Twelve healthy subjects (six men and six women) with no history of abdominal or lower back pain within 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Previous studies focused on decreased SCM and increased abdominal activity during the curl-up exercise 13 , 14 ) . Yoon et al 14 ) reported that the muscle activity of SCM during curl-up with craniocervical flexion (CCF) was significantly lower than during the traditional curl-up exercise, but the abdominal muscle activity did not differ between the two tasks. However, we found that decreased SCM activity could influence increased abdominal muscle activity during curl-up with neck flexion restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on decreased SCM and increased abdominal activity during the curl-up exercise 13 , 14 ) . Yoon et al 14 ) reported that the muscle activity of SCM during curl-up with craniocervical flexion (CCF) was significantly lower than during the traditional curl-up exercise, but the abdominal muscle activity did not differ between the two tasks. However, we found that decreased SCM activity could influence increased abdominal muscle activity during curl-up with neck flexion restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The participant was laid in the supine position with hips and knees flexed 90°, feet were supported, and the trunk was maximally flexed and rotated to the right, for the IO/TA MVIC evaluation. The examiner applied manual resistance at the shoulders by pushing the trunk extension and left rotation directions (19,20). MVIC testing was repeated three times.…”
Section: Electromyography (Emg)mentioning
confidence: 99%